The economics of recreational park conservation : a case study of Bako National Park - Awang Marikan, D. A.; Radam, A.; Zakaria, Joh (Universiti Malaysia Sarawak, (UNIMAS), 2000)
The research is done to estimate the individual WTP for conservation of outdoor recreational places with the case study on the Bako National Bako, Kuching, Sarawak. The dichotomous choice of CVM is used in this study conducted through questionnaires. This is to identify the factors that affect the visitors/respondents WTP, estimating the maximum and minimum level they are willing to pay for conservation and preservation motive and at what price level they are capable of paying on the average. Further more, the logit model also is used to analysed the data and the maximum likelihood estimates of this model is encouraging. The median value of WTP for preservation of Bako National Park is estimated to be RM7.765 per person. The results of this study can be used by Bako National Park management as an information guideline for their preservation future plan and campaign especially for virgin forest, swamp forest, beaches and other non market resources.